2017
DOI: 10.1053/j.gastro.2017.06.053
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Liver Offers to Pediatric Candidates on the Transplant Wait List

Abstract: BACKGROUND & AIMS: Approximately 10% of children on the liver transplant wait-list in the United States die every year. We examined deceased donor liver offer acceptance patterns and their contribution to pediatric wait-list mortality. METHODS: We performed a retrospective cohort study of children on the US liver transplant wait-list from 2007 through 2014 using national transplant registry databases. We determined the frequency, patterns of acceptance, and donor and recipient characteristics associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
91
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(92 citation statements)
references
References 13 publications
0
91
0
1
Order By: Relevance
“…Our analysis also attempted to quantify the degree to which increased use of SLT could potentially reduce wait‐list mortality and determined that most children who die on the waiting list were waiting for at least a week, and approximately half of these children met criteria for being an optimal recipient for SLT with a predicted graft survival that would be similar for SLT and WLT. These findings should be considered in the context of work by Hsu et al that showed nearly half of the children who died on the waiting list never received a single offer of a liver . Furthermore, recent research by Perito et al showed that approximately half of the most splitable livers, by strict criteria, were not used for SLT …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our analysis also attempted to quantify the degree to which increased use of SLT could potentially reduce wait‐list mortality and determined that most children who die on the waiting list were waiting for at least a week, and approximately half of these children met criteria for being an optimal recipient for SLT with a predicted graft survival that would be similar for SLT and WLT. These findings should be considered in the context of work by Hsu et al that showed nearly half of the children who died on the waiting list never received a single offer of a liver . Furthermore, recent research by Perito et al showed that approximately half of the most splitable livers, by strict criteria, were not used for SLT …”
Section: Discussionmentioning
confidence: 91%
“…Pediatric liver transplantation (LT) provides lifesaving therapy for children with end‐stage liver disease and other metabolic conditions but continues to be hindered by a scarcity of available organs . Wait‐listed children typically receive fewer offers for deceased donor organs than adults, suggesting that they are especially vulnerable to an imbalance in need and availability . Consequently, neonates have the highest rate of wait‐list mortality for any age group with nearly one‐third of wait‐listed neonates dying before receiving a suitable offer …”
mentioning
confidence: 99%
“…Historically, these grafts are carried out at select centers and considered higher risk due to increased technical complexity and difficult donor selection . As a result, the decision‐making process around waiting for a size‐matched whole graft versus making the best of a TVG opportunity remains challenging . This study is the first to comprehensively evaluate TVG in PALF patients in a national experience.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has plateaued (11%, 16%, 16% in 1995, 2005, 2015, respectively) despite a nearly 10:1 ratio of splittable donor organs, using the ideal donor definitions provided by Toso et al It seems that technical and logistical challenges could have affected surgeon's preference to determine whether such ideal donors are used for SRLT. However, it may also reflect the ongoing allocation disparity in splitting between adult and pediatric transplantation . Although our study demonstrated improved wait‐list outcomes for patients listed at a center with a high volume of TVG transplantations, there are logistical challenges associated with transferring PALF patients to high‐volume centers.…”
Section: Discussionmentioning
confidence: 99%
“…Waitlist mortality in children awaiting LT remains high, with rates of 12%‐15% in patients <2 years of age . To improve on this, it is critical for pediatric liver transplant centers to find alternate strategies to mitigate this risk of waitlist mortality by increasing donor availability and effective organ allocation . Interest in ABO‐ILT has recently been renewed for select patients to broaden the donor pool and result in timelier LT .…”
Section: Introductionmentioning
confidence: 99%